STRATEGI PENGUATAN MARKETING SKILL DI ERA DIGITAL: ANALISIS KOMPETENSI DAN DAMPAKNYA TERHADAP KINERJA PENJUALAN - Imel Santika Siregar; Zuhrinal M. Nawawi (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Digital transformation has significantly reshaped the marketing landscape, requiring entrepreneurs and sales personnel to possess strong digital marketing competencies. This study aims to analyze strategies for strengthening marketing skills in the digital era and their impact on sales performance, particularly in the SME sector. The method used is a literature study with a qualitative approach, focusing on scientific articles from 2020–2024. The analysis reveals that digital marketing skills, such as social media use, SEO, and content marketing, positively influence sales target achievement. Competencies in digital data analysis, product knowledge, and creativity in marketing campaigns have been shown to improve sales effectiveness. However, several challenges remain in implementation, such as limited human resources, technological infrastructure, and cybersecurity. Therefore, strengthening marketing skills must be supported by continuous training and systemic support to optimally impact business growth.